(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article is dedicated to the peculiarities characteristic of the new generation of designers and architects who have embraced the design possibilities of the so-called digital era. It examines the distinctions between level design and architecture, focusing on their objectives and creation context. While there are numerous intersections and interactions between level design and architecture, both disciplines involve creating spaces for people. Nevertheless, there are significant differences that need to be considered when teaching architecture students about level design. This article discusses some of these differences and offers recommendations for teaching level design within the context of architectural education. Level design is the process of creating game locations that provide an interesting and engaging gaming experience. Level designers utilize various techniques and tools to shape space, atmosphere, tasks, and challenges for players. Level design requires knowledge of game design, architecture, psychology, art, and programming. Architecture is the art and science of designing buildings and other physical structures. It deals with the form, function, aesthetics, social aspects, and durability of space. Architects employ various methods and tools to develop concepts, plans, models, and documentation for their projects. Research conducted within the scientific activities of the Drawing, Painting, and Architectural Graphics Department, the Department of Architectural Design, and the Department of Architecture and Urban Planning indicates the necessity of considering innovative educational processes as part of architects’ practical activities aimed at adapting students to innovations. The article addresses issues regarding the utilization of research findings in the development and improvement of departmental disciplines for architecture students and the methodology for representing an interactive approach to teaching, which fosters the thinking of future architects. It also explores one of the contemporary issues – game development – as one of the methods of using alternative contemporary architecture. The necessity of integrating traditional academic and innovative approaches in teaching representation as a comprehensive subject in the architect and designer professions is justified. A classification of approaches to level design as a tool for realizing ideas of "paper architecture" in the works of architecture students and graphic designers is provided. The article discusses current approaches in education and their reflection in architectural and graphic solutions in higher education institutions based on an analysis of international experience. Conceptual and practical solutions in the field of representing architectural spaces in higher education institutions that correspond to current changes in the educational process system are identified.